Traditional Wisdom: Folktales from Uganda - Dipio, Dominica; Sillars, Stuart (Nairobi ComMattersKenya(CMK), 2012)
This book is the latest fruit from Makerere's long and passionate engagement with oral art. Although it focuses on the folktale, the collection gives us valuable insights into other forms of orature, since there is always an 'interfluence' among various genres The proverb blossoms into narrative, just as easily as it sums up the story and the whole performance is animated with strong drama.......
This book is the latest fruit from Makerere's long and passionate engagement with oral art. Although it focuses on the folktale, the collection gives us valuable insights into other forms of orature, since there is always an 'interfluence' among various genres The proverb blossoms into narrative, just as easily as it sums up the story and the whole perfomance is animated with strong drama.......